Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns - Southeast Asian Regional Center for Graduate Study and Research in Agriculture (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2021)
Structural transformation in Southeast Asia poses challenges to the regions' food security and inclusive agricultural growth agenda. Integration of agricultural markets within ASEAN is high on the policy agenda given the current pressure on moving towards the establishment of a common market. This process though, may prove unattainable unless appropriate policies and strategies are designed to defuse food security and rural poverty concerns among policymakers and stakeholders. An improvement in agricultural value chains' competitiveness is supportive of the broader effort towards achieving competitive ASEAN economies. Two fundamental concerns arise in this regard, though. First, regional supply chains in key crops are increasingly crossing borders raising fears among primary producing countries of a loss of sovereignty and of missed opportunities for domestic industrialization and value addition. Corn, rice, livestock, and vegetables sourced from Lao PDR and Cambodia and processed and retailed in Thailand and Vietnam for subsequent re-export outside ASEAN are an example in case. Second, farm diversification out of traditional staple crops may be at variance with national and/or rural food security strategies. For instance, modernization of rice and corn value chains in the Philippines and Indonesia have been at variance with governments' efforts to achieve self-sufficiency. Furthermore, with a growing urban population, food price shocks are perceived as a major threat by all countries in the region, leading to sub-optimal policy outcomes at the national and regional level. Yet, both concerns are in need of a re-examination given the rapid transformation of Asia's farming systems and urban consumption patterns, and the associated growing pressures for farm mechanization, downstream industrialization, diversification of rural livelihoods, and adoption of more stringent food safety and quality standards.